Cerebellar direct current stimulation modulates hand blink reflex: implications for defensive behavior in humans - Bocci, Tommaso; Ferrucci, Roberta; Barloscio, Davide; Parenti, Laura; Cortese, Francesca; Priori, Alberto; Sartucci, Ferdinando (Physiological reports, 2018)
The cerebellum is involved in a wide number of integrative functions. We evaluated the role of cerebellum in peripersonal defensive behavior, as assessed by the so‐called hand blink reflex (HBR), modulating cerebellar activity with transcranial direct current stimulation (tDCS). Healthy subjects underwent cerebellar (sham, anodal, and cathodal tcDCS) and motor cortex tDCS (anodal or cathodal; 20′, 2 mA). For the recording of HBR, electrical stimuli were delivered using a surface bipolar electrode placed on the median nerve at the wrist and EMG activity recorded from the orbicularis oculi muscle bilaterally. Depending on the hand position respective to the face, HBR was assessed in four different conditions: “hand‐far,” “hand‐near” (eyes open), “side hand,” and “hand‐patched” (eyes closed). While sham and cathodal cerebellar stimulation had no significant effect, anodal tcDCS dramatically dampened the magnitude of the HBR, as measured by the area under the curve (AUC), in the “hand‐patched” and “side hand” conditions only, for ipsilateral (F(4,171) = 15.08, P < 0.0001; F(4,171) = 8.95, P < 0.0001) as well as contralateral recordings (F(4,171) = 17.96, P < 0.0001); F4,171) = 5.35, P = 0.0004). Cerebellar polarization did not modify AUC in the “hand‐far” and “hand‐near” sessions. tDCS applied over the motor area did not affect HBR. These results seem to support a role of the cerebellum in the defensive responses within the peripersonal space surrounding the face, thus suggesting a possible cerebellar involvement in visual‐independent defensive behavior. We evaluated the role of cerebellum in peripersonal defensive behavior. Cerebellum modulates defensive behavior when the visual feedback is missing. Cerebellum may be involved in visual‐independent learning of defensive behavior.